National and Cultural Features of Color-Component Language Units in Materials of the Spanish and Uzbek Languages - Karayeva Nargiza Abdugapurovna, (European Journal of Life Safety and Stability (2660-9630), 2024)
The Uzbek language is extremely rich. Then you can express your opinion in several ways, changing it in a positive or negative direction through the color of one word. In today's article, we will highlight the national-cultural features of language units with a color component.